THE IMPORTANCE OF USING THE BUDGET IN THE FINANCIAL PLANNING PROCESS IN IRAQI PRIVATE BANKS - Prof. Assistant Arshed Makki Rasheed; Prof. Assistant Ahmed Rahi Abd (Scholars Digest Publishing, 2023)
The research aims to indicate the importance of the budget in the financial planning process and whether it is of importance to the various administrative (50) questionnaires were distributed to a number of department and branch managers in banks (Al- Khaleej Commercial Bank, Sumer Commercial Bank, Iraqi Investment Bank, Ashur International Investment Bank, and Al-Mansour Investment Bank). The research used a set of statistical methods such as Cronbach's alpha coefficients and the coefficient of stability and validity of the used questionnaire, as well as the use of linear regression and correlation and the t and F tests. About the participation of the various departments within the banks in formulating the items of the balance sheet The researchers also proposed a set of recommendations and proposals, most notably: the need for banks to pay attention to the function of financial analysis as a preparatory and prior tool for financial planning and to rely on statistical methods in estimating the values of budgets to ensure the preparation of more accurate budgets.